Microcontroller Based Variable Frequency Power Inverter - A. Ahmed, Khalid Ali Madi (2007)
The variable frequency inverters have been used in wide applications, such as speed control of induction motors. The variable speed operation of a single phase and three-phase induction motors suffer from large harmonic and limited speed range. Therefore, intensive researches were carried out in order to eliminate the harmonic distortion, simplify the motor speed control task over a wide range, and to reduce the overall system cost. This work investigates performance of the microcontroller based variable frequency power inverter to reduce the Total Harmonic Distortion (THD) for the overall system. The fully controlled single phase and three-phase bridge voltage source inverter have been designed and implemented with semiconductors power devices Insulated Gate Bipolar Transistor. The microcontroller has been employed in this inverter to provide SPWM signal that controls the applied voltage on the gate drive, which provides the desired SPWM frequency at the output of the power inverter.